EFFECT OF ORGANIZATIONAL COMPETENCE, ORGANIZATIONAL SUPPORT, AND ORGANIZATIONAL PRODUCTIVITY TOWARDS ADOPTION OF FINANCIAL TECHNOLOGY - Herdinata, Christian; Wiradinata, Trianggoro; Christian, Sonata; Setiobudi, Auditia (Universitas Brawijaya, Indonesia, 2019)
The rapid development of internet technology with affordable prices raises new opportunities for micro, small, and medium enterprises (SMEs) in East Java in creating product innovation and marketing development. Various studies in the field of entrepreneurship and information technology have been carried out, but not many studies specifically examine the level of adoption of the Financial Technology system for business creation and development. This study focuses on the influence of organizational competence, organizational support, organizational productivity on financial technology adoption. This study uses a quantitative approach with a sample of SME businesses that use financial technology system adoption in the business that is run. The sample chosen using purposive sampling technique and selected 402 SMEs in East Java with the data analysis technique used is multiple linear regression techniques. The results of this study found that the influence of organizational competence, organizational support, and organizational productivity had a significant influence on financial technology adaptation.